Evaluation of diagnostic methods for detection of trichomoniasis in symptomatic women with vaginal discharge - Mishra, Gargee; Gupta, Kavita; Mohanty, Srujana; Mitra, Subarna; Singh, Arvind Kumar (The Journal of Infection in Developing Countries, 2025)
Introduction: Vaginal discharge is a common gynecological condition among reproductive age women. Common infections include bacterial vaginosis (BV), vulvovaginal candidiasis (VVC), and trichomoniasis. Prevalence of trichomoniasis varies with geographical area and the diagnostic techniques used. This study was conducted to compare various diagnostic methods for detection of trichomoniasis among women of the reproductive age group. Methodology: The study was conducted from January 2021 to July 2022, and 114 patients were included. Vaginal discharge was collected from the lateral wall of the vagina and posterior fornix using four swabs for bedside culture into Kuperberg media, polymerase chain reaction (PCR), wet mount, Giemsa staining, Gram staining, and culture on blood agar for Candida spp. Nugent scoring in Gram stain was used to determine BV. Result: BV was identified in 21.05% (24/114), VVC in 6.14% (7/114), and Trichomonas vaginalis (TV) in 4.4% (5/114) by PCR. However, TV was detected only in three patients by wet mount, Giemsa stain, and culture. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for wet mount and Giemsa stain were 100% for each parameter compared to culture; while sensitivity and specificity were calculated as 100% and 98.2% for PCR. All patients with TV presented with greenish frothy discharge (pH > 4.5) and vaginal wall inflammation. Conclusions: Culture remains the standard diagnostic approach and is cost effective; but it has major shortcomings such as the need for faster sample transportation and longer turnaround time. PCR can detect non-viable trichomonads and can provide early and accurate diagnosis.